PENERAPAN MEDIA PEMBELAJARAN LUDO NARASI SEJARAH BERBASIS CULTURALLY RESPONSIVE TEACHING (CRT) UPAYA PENINGKATAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN JATISARI SEMARANG - Ita Mutiara Dewi; Panca Dewi Purwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of utilization of innovative learning media and classroom reading corners during learning at SDN Jatisari Semarang has an impact on students' reading comprehension skills in the Indonesian Language subject. The purpose of this study was to describe the steps of implementing the Ludo Narasi Sejarah learning media based on Culturally Responsive Teaching (CRT) and to test the effectiveness of the Ludo Narasi Sejarah learning media based on CRT in improving the reading comprehension skills of fourth grade students at SDN Jatisari Semarang. This study used a combination method (mix method) that collected quantitative and qualitative data simultaneously. The qualitative method used was descriptive qualitative whose data was obtained from the application of the Ludo Narasi Sejarah learning media based on CRT. The quantitative method used was the pretest-posttest one group design whose data was obtained from the pretest and posttest. The results of the study showed that the application of the Ludo Narasi Sejarah learning media based on CRT with a cooperative learning model consisted of 6 stages, namely conveying objectives and motivating students, presenting information, organizing students in groups, guiding study groups, evaluating, and giving awards. Based on the results of the pretest and posttest, it is known that the Ludo Narasi Sejarah learning media based on CRT is effective in improving students' reading comprehension as indicated by the average pretest score of 58 to 80.14 during the posttest, and the N-Gain test results obtained a value of 0.52 with moderate criteria. From these results, it can be concluded that the application of the Ludo Narasi Sejarah learning media based on CRT is effective in improving the reading comprehension of fourth grade students of SDN Jatisari Semarang.